Aproximando Indústria e Academia para Lapidação de Talentos em Desenvolvimento de Software no Sertão do Ceará: Um Estudo de Caso sobre o mandacaru.dev - Feitosa, Alexandre; Tavares, Artelino; Martins, Henrique; Pessôa, Emanuel; Paiva, Marlon; Tomaz, Emerson B.; Araújo, Allysson Allex (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
Grounded on the alliance between industry and academia, mandacaru. dev emerged to nurture talent from the of Ceará through an immersive training program aligned with the digital challenges of companies B3, Bolsa do Brasil, PDtec, and BLK, in partnership with the Federal University of Ceará (UFC). As a descriptive case study, this study seeks to investigate the perception of students (n=72) and professionals (n=8) involved in the organization/execution of mandacaru.dev. Quali-quantitative research utilized questionnaires and interviews for data collection, with Descriptive Statistics and Thematic Content Analysis were applied for data analysis. In summary, 77.77% of students saw positive professional growth from mandacaru.dev, while 87.50% felt more connected to the software market. The qualitative analysis covered prior experience and expectations, operationalization of the program, and implications and lessons learned. This research contributes to academia and industry by examining, from the perspectives of students and professionals, a relevant experience rooted in industry-academia collaboration aimed at training and attracting talent in software development.